(untitled) (Journal of Plant Disease Sciences, 2021)
Sweet orange is one of the most remunerative fruit crops of India, having a lasting niche in the international trade and world finance. Several diseases are responsible for Sweet orange decline in which dry root rot disease caused by Fusarium solani is more prevalent. Carbendazim 12% +mancozeb 63% WP recorded least per cent disease incidence (20.0%) of dry root rot at 60 days after transplanting of seedlings with highest percent disease reduction of 78.57% and found at par with the treatment metalaxyl 8% + mancozeb 64% WP that recorded 22.22 % per cent disease incidence and 76.19% percent disease reduction over control. Whereas, treatment of compost agriculture waste was found least effective with comparatively more disease incidence over rest of the fungicidal treatments.